FAKTOR RESIKO DAN MANAJEMEN PTERIGIUM PADA PENDUDUK DAERAH PESISIR - Naurah Nazhifah; Hamsu Kadriyan (Jurnal Inovasi Pendidikan dan Sains, 2022)
Pterygium comes from the Greek, namely pteron, which means wing. Pterygium is an abnormal growth of fibrovascular tissue with a triangular shape from the conjunctiva that extends to the cornea. It is a proliferative disorder of the ocular surface, caused by connective tissue remodeling and angiogenesis leading to fibrovascular proliferation. This journal aims to provide information about risk factors and management of pterygium in coastal residents. Work as a farmer/fisherman/labourer had the highest prevalence of pterygium at 15.8%. The most influential pterygium risk factor for coastal communities is their work as a fisherman, and also being in the equatorial area which is an area with high sun exposure, this can trigger pterygium. Work as a fisherman carried out for years and hours, which averages around 7 hours and above for exposure to direct sunlight can also trigger pterygium. Pterygium management that can be done is giving eye drops to reduce complaints, then performing surgery or surgery using excision techniques, namely baresclera, Conjunctival autograft technique, and Amniotic membrane grafting. The high recurrence rate associated with postoperative complications is common thus additional medical management has been included in the surgical treatment of pterygium namely mitomycin C, anti-VEGF, 5-fluorouracil (5-FU) and loteprednol etabonate.